A closer look into the nitrogen blank in elemental analyser/isotope ratio mass spectrometry measurements. (2nd November 2017) - Langel, Reinhard; Dyckmans, Jens
Abstract : Rationale: One important limitation for the precise measurement of minute amounts of nitrogen (N) in solid samples by elemental analyser/isotope ratio mass spectrometry (EA/IRMS) is the accurate determination of the analyser blank value. This study was performed to identify different sources, amounts and isotopic composition of N blanks in EA/IRMS in order to identify measures for minimising the effect of the N blank on N isotopic data quality. Methods: Different types of autosamplers, with and without zero‐blank functionality, were tested by analysing different amounts of substances of varying isotopic composition by EA/IRMS. Results: Using zero‐blank autosamplers reduces the atmospheric N2 blank from 60 nmol to between 4 and 5 nmol depending on the autosampler type. This blank is derived from atmospheric N2 leaking into the elemental analyser, trapped in the sample tin capsules or contained in the oxygen added for combustion. Another source of blank is the reaction tube. As the sources of the blank differ, the isotopic composition of the blank is very variable. In addition, cross‐contamination from previous samples may contribute up to 3.3 nmol N. Conclusions: For precise measurements of minute amounts of N in solid samples, reduction of the N blank is the most promising strategy. Correcting for the remaining N blank is only meaningful if the sample isotopic composition is very different from that of the N blank, because the precise determination of the isotopic composition of the N blank is not possible.